Delivering health and nutrition interventions for women and children in different conflict contexts: a framework for decision making on what, when, and how. Issue 10273 (6th February 2021) - Gaffey, Michelle F; Waldman, Ronald J; Blanchet, Karl; Amsalu, Ribka; Capobianco, Emanuele; Ho, Lara S; Khara, Tanya; Martinez Garcia, Daniel; Aboubaker, Samira; Ashorn, Per; Spiegel, Paul B; Black, Robert E; et al.
Summary: Existing global guidance for addressing women's and children's health and nutrition in humanitarian crises is not sufficiently contextualised for conflict settings specifically, reflecting the still-limited evidence that is available from such settings. As a preliminary step towards filling this guidance gap, we propose a conflict-specific framework that aims to guide decision makers focused on the health and nutrition of women and children affected by conflict to prioritise interventions that would address the major causes of mortality and morbidity among women and children in their particular settings and that could also be feasibly delivered in those settings. Assessing local needs, identifying relevant interventions from among those already recommended for humanitarian settings or universally, and assessing the contextual feasibility of delivery for each candidate intervention are key steps in the framework. We illustratively apply the proposed decision making framework to show what a framework-guided selection of priority interventions might look like in three hypothetical conflict contexts that differ in terms of levels of insecurity and patterns of population displacement. In doing so, we aim to catalyse further iteration and eventual field-testing of such a decision making framework by local, national, and international organisations and agencies involved in the humanitarian health response for women and children affected by conflict.